Yarn and fabric properties in a modified ring spinning system considering the effect of the friction surface of the false-twister - Yin, Rong; Tao, Xiao-Ming; Xu, Bin-gang (Textile research journal, 2020)
This paper experimentally studies the relationship between the friction surface of a false-twisting unit and the quality of cotton yarns produced by a modified ring spinning system, with the adoption of the single friction-belt false-twister. The friction surface of the false-twisting unit, as a key twisting component, has been studied in terms of material, surface roughness, hardness and diameter, as well as the interaction between these factors and resultant yarn properties, with particular attention to yarn imperfections. Experimental results showed that the false-twisting unit with a short interactive path demonstrated significant reduction of yarn imperfections, especially yarn neps. With the optimal false-twisting unit, performances of the modified yarns and their knitted fabrics were evaluated and compared with the conventional ones.